Long-term intervention of at-risk elementary students' socio-motivational and reading comprehension competencies: Video-based case studies of emotional support in teacher-dyad and dyadic interactions - Salo Anne-Elina; Vauras Marja; Hiltunen Maiju; Kajamies Anu (ELSEVIER SCI LTD, 2022)
The intertwining of peer and teacher emotional support patterns for enhancing at-risk students' multi-perspective academic competencies remains scarcely mapped. The multi-level analysis in the present study uncovers emotional support trajectories within teacher-dyad and dyadic interaction contexts among at-risk elementary students over a three-semester computer-supported intervention. A cluster analysis was conducted for all students (n = 318), where most intervention students had cumulated risks in socio-motivational and reading competencies. The time spent by 12 dyads within the two interaction contexts was analyzed from a vast amount of video data. The results suggested that simply allocating support time may be insufficient and its quality should be scrutinized. An in-depth video analysis of four dyads, illustrated with interaction excerpts and summary figures, indicated that teachers differed in their ability to calibrate their emotional support dynamically. The dyadic interactions of at-risk students were mostly on-task and neutral or positive. The intertwining of teacher-dyad and dyadic emotional support indicated that mechanisms positively contributed to enhancing multi-perspective academic competencies, although some risks were noted. Acknowledging the emotional states of others and successfully regulating one's own emotions were critical. Thus, infusing support for emotional competence and regulation strategies into both teacher and basic education is recommended.